Use of Songs Media in Listening Learning in Class III Elementary School - Iqbal Yusca Ismail; Vismaia Damayanti (Universitas Sebelas Maret, 2019)
This research based on low of student’s listening skill in learning English at Madrasah Ibtidaiyah Al-Falaah Kopo. The learning process seems just apply teacher centered method. It makes students unmotivated in learning English especially in listening skill. Therefore, the researcher make serious efforts to use songs in teaching listening in order to make the learning process being fun and interesting. The aims in this research is to get the description of student’s learning outcome improvement in teaching listening using song as a media. The research used classroom action research with Elliot models by implementing three cycles and there are three actions in each cycles. The subject of this research were 3th grade students of Madrasah Ibtidaiyah Al-Falaah Kopo consist of 17 male students and 17 female students. Based on the result of this research, it can be concluded that there is an improvement in the score average of the students. In the first cycle, student’s average is 60, and second cycle is 64, and in the third cycle is 75. Therefore the use of songs as a media could improve student’s learning outcomes and it can be a recommendations or suggestions for teachers to teach English or in other education research.